Menstrual hygiene knowledge and practices among high school girls in urban central India: a cross-sectional study - Rajput, Kiran B.; Mangla, Vipra; Bhargava, Akash; Tawar, Shabeena; Singh, P. M. P. (International Journal Of Community Medicine And Public Health, 2025)
Background: Menstruation is a natural physiological process, yet many adolescent girls in India lack adequate knowledge and face challenges in managing menstrual hygiene. Inadequate menstrual hygiene practices can lead to reproductive tract infections (RTIs) and other health issues. This study aimed to explore menstrual hygiene knowledge and practices among high school girls in urban central India, contributing to the understanding of current status of menstrual hygiene management in this region. Methods: A school-based cross-sectional study was conducted among 1160 high school girls (grades 9th to 12th) in three government schools in an urban region of central India. The participants were surveyed using a self-administered questionnaire assessing their knowledge and practices related to menstruation and menstrual hygiene. Data were analyzed using descriptive statistics and logistic regression to identify predictors of menstrual knowledge and hygiene practices. Results: Of the 1160 participants, 52.5% exhibited good knowledge, while 42.1% demonstrated good menstrual hygiene practices. The majority (96.4%) used sanitary pads, but 35.9% did not change them at least three times a day, exposing them to potential health risks. Factors influencing good menstrual knowledge and hygiene practices included maternal education, age, family income and grade level. Conclusions: Despite a relatively high level of awareness about menstruation and hygiene, significant gaps remain in understanding menstrual biology and practicing optimal hygiene. Socio-economic factors and parental education play a critical role in improving menstrual hygiene knowledge and practices among adolescent girls.